A comparative study of dielectric, ferroelectric and magnetic properties of BiFeO3 multiferroic ceramics synthesized by conventional and spark plasma sintering techniques. Issue 1 (January 2015) - Song, S.-H.; Zhu, Q.-S.; Weng, L.-Q.; Mudinepalli, V.R.
Abstract: BiFeO3 ferrite ceramics were synthesized by spark plasma sintering (SPS) and conventional solid-state synthesis in conjunction with high-energy ball milling. They were evaluated by different characterization techniques such as X-ray diffraction, scanning electron microscopy, and dielectric, ferroelectric and magnetic measurements. The 750 °C-SPS prepared ceramic samples possessed a single perovskite structure and they were compared with the conventionally synthesized ones. The relative density and average grain size were approximately 95% and <200 nm for the SPS-prepared samples, while they were about 89% and >300 nm for the conventionally prepared ones. In comparison with the conventionally synthesized ceramics, the SPS-prepared ones exhibited improved dielectric, ferroelectric and magnetic properties. These should be associated with high-density, fine-grained and uniform microstructure created by SPS in conjunction with high-energy ball milling, which could be a promising technique for fabricating high-quality BiFeO3 multiferroic ceramics.